(untitled) (Triyuga Academic Journal, 2025)
Mobile phones have become integral tools in higher education, significantly shaping students’ learning experiences, social interactions, and daily routines. At Triyuga Janata Multiple Campus (TJMC), students widely use mobile devices for both academic and non-academic purposes, reflecting a growing trend of digital technology adoption among youth. This study explores the patterns, purposes, and impacts of mobile phone usage among TJMC students, emphasizing both benefits and challenges. Findings indicate that 70% of students use mobile phones for academic activities such as attending online classes, accessing e-books, conducting research, and using educational apps, while 85% spend significant time on social media and gaming, which can reduce study efficiency. Additionally, 95% of students rely on phones for communication with teachers and peers. The study highlights positive outcomes, including quick access to study materials, enhanced collaboration, and support for self-paced learning, as well as negative effects like distraction, sleep disturbance, procrastination, and reduced concentration. These insights can inform strategies to promote responsible mobile phone use and maximize academic benefits while mitigating adverse impacts on student well-being.